EDUCOMMUNICATION, OR FACING THE UNFAIR COMPETITION BETWEEN EDUCATION AND THE MEDIA SPECTACLE - Fortunato, Ivan [UNESP]; Camargo Penteado, Claudio Luis de (Univ Estadual Campinas, Fac Educacao, 2015)
Facing the contemporary media centrality, we present this literature review and critical reflection paper, based in sociological studies and the purposes of a new area called Educommunication. By collating the literature with our own experience as university professors, our main goal is to present some critics to the media content, which acts as a kind of unfair competition to the educational work conducted in schools and universities. First, it is considered that in its historical development, media outlets took the central role in the organization of social life, in a broad sense, embracing the political, cultural, and even axiological dimensions of contemporary society. Second, we discuss what we name as unfair competition between media and education, based on the huge amount of media products developed from the perspective of the spectacle. Finally, we emphasize the educational communication as a potential cooperation to educational work.
Keywords: Media; Miseducation; Educommunication